KEBERAGAMAAN MAHASISWA KOS SEKOLAH TINGGI AGAMA ISLAM NEGERI PALANGKA RAYA - Fadli, Syairil (Jurnal Studi Agama dan Masyarakat, 2013)
This study departed from two problems: 1) the religious behavior of boarding students of State Islamic College (STAIN) Palangka Raya and 2) the influence of religion on social life of boarding students of State Islamic College (STAIN) Palangka Raya. The research data was obtained by using field research and library research. After getting all of information which the writer had collected in the field, the data was processed quantitatively by using reflective-systematic method. The results of this study reflected that religious behavior boarding students of State Islamic College (STAIN) Palangka Raya positive behavior, this could be seen from their ethusiasm in carrying out good worship prayer, worshipping in the month of Ramadhan such as tarawih prayer and reciting the Quran, and commemorating the great days of Islam actively. Meanwhile the influence of religion in social life behavior was seen in their life peacefulness, no worries, open and commodious feelings, feeling alive and friendly towards each other or others in general, morale in carrying out activities, and realizing the nature and human mind that the events in human life did not happen automatically.